2011
DOI: 10.1002/med.20222
|View full text |Cite
|
Sign up to set email alerts
|

Endomorphins: potential roles and therapeutic indications in the development of opioid peptide analgesic drugs

Abstract: The application of endomorphins as clinical available analgesic drugs has been impeded by their relatively poor receptor selectivity compared with alkaloid analgesics, rapid degradation in vivo, inefficient to penetrate the blood-brain barrier (BBB), and undesirable or toxic effects, such as acute tolerance and physical dependence, respiratory depression, and inhibition of gastrointestinal motility. Extensive studies have been performed so far striving to conquer these problems. In this article we review and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 163 publications
0
61
0
1
Order By: Relevance
“…As we know, peptide and protein drugs hold great promise for the treatment of brain disorders (Hökfelt et al, 2003;Liu and Wang, 2012;Selkoe, 2001). Nevertheless, their poor transfer through the BBB leads, typically, to failure to reach the target after systemic administration.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, peptide and protein drugs hold great promise for the treatment of brain disorders (Hökfelt et al, 2003;Liu and Wang, 2012;Selkoe, 2001). Nevertheless, their poor transfer through the BBB leads, typically, to failure to reach the target after systemic administration.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the Phe 4 in the parent peptide, both the aromatic group and the backbone structure of Map were highly constrained, and this limitation of the conformational flexibility could be regarded as an efficient strategy for BBB permeability (Keresztes et al, 2010;Guillemyn et al, 2012). In addition, the improved CNS penetrating efficacy of EM-1 has previously been achieved by second-site or multiple-site modifications (Keresztes et al, 2010;Liu and Wang, 2012), and our study indicated that the C-terminus is another potential site to regulate the BBB permeability of EM-1.…”
Section: Discussionmentioning
confidence: 98%
“…However, the inability of EM-1 to pass through the BBB has greatly hampered its clinical development (Tomboly et al, 2002;Janecka et al, 2008;Liu and Wang, 2012). In our previous study, we described a series of EM-1 analogues (termed MELs) obtained by chemical modifications that showed improved in vitro characteristics as compared to the parent peptide Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8 In 1997, highly selective m-peptides, termed endomorphins, were added to the roster of endogenous ligands. [9][10][11] Opioid receptors belong to the family of metabotropic membrane receptors that couple via the Gi/Go subtypes of G proteins to cellular transduction processes. The opioid receptors are widely distributed throughout the body; those involved in pain modulation are found in the central nervous system and the peripheral nervous system; opioid receptors are also found on cells of the immune system, [12][13][14] throughout the enteric nervous system of the gastrointestinal tract 15 and elsewhere.…”
mentioning
confidence: 99%